The flexible enterprise - Stohr, Edward A.; Sushil (Flexible Systems Management, 2014)
The need for enterprise flexibility in an era of rapidly advancing technology, increasing competition, and globalization, is apparent. Flexibility can be thought of as an ability of the enterprise to quickly and efficiently respond to market changes and to bring new products and services quickly to the market place. Beyond this definition, a truly flexible enterprise should proactively change the market through its ability to create new and innovative products and services. The proposed book is intended to provide a conceptual framework of 'Flexible Enterprise' supported by researches/case applications in different types of flexibilities exhibited by a flexible enterprise. The selected papers covering a variety of issues concerning the planning and operation of a flexible enterprise are organized into following four parts: I Enterprise and Strategic Flexibility II Organizational Flexibility III Business Process and Information Systems Flexibility IV Operations Flexibility